Risk factor assessment and microbiome analysis in peritoneal dialysis-related peritonitis reveal etiological characteristics - Zhang, Li; Zhang, Hongrui; Su, Sensen; Jia, Ye; Liang, Chenyang; Fang, Yuan; Hong, Dengwei; Li, Tianyu; Ma, Fuzhe (Frontiers in Immunology, 2024)
BackgroundPeritoneal dialysis-related peritonitis (PDRP) is one of the most common complications of peritoneal dialysis (PD). Understanding the risk factors and etiological characteristics is indispensable for infection prevention and improving the outcome and life quality.MethodsA total of 70 PD patients were separated into the PDRP group (n=25) and the control group (n=45). Variables, including gender, age, body mass index, primary diseases, and history of basic diseases, in the two groups were analyzed to assess the risk factors of PDRP. Metagenomic next-generation sequencing (mNGS) and microbial culture were compared in detecting pathogenic microorganisms. Gut microbiota analysis was performed in 35 PDRP patients based on mNGS data.ResultsDialysis time and times of dialysate change were the risk factors of PDRP, and times of dialysate change was the independent risk factor of PDRP (p = 0.046). mNGS produced higher sensitivity (65.79%) than microbial culture (36.84%) in identifying pathogenic microorganisms. Staphylococcus aureus and Klebsiella pneumoniae (four cases) were the most frequent pathogens causing PDRP, followed by Staphylococcus capitis (three cases). β diversity of the gut microbiota was significantly different between patients with fewer times of dialysate change (≤4) and more (>5), as well as between patients with gram-positive (G+) bacterial and gram-negative (G−) bacterial infection.ConclusionThe dialysis time and times of dialysate changes not only are risk factors for peritonitis in PD patients but also stimulate significant changes in the gut microbiome structure in PDRP patients. These findings may provide a novel viewpoint for the management of patients with PDRP.